Maresin1 Alleviates Ischemia Reperfusion Injury After Lung Transplantation by Inhibiting Ferroptosis via the PKA-Hippo-YAP Signaling Pathway - Peng Deng; You Wu; Li Wan; Xiangfu Sun; Quanchao Sun (Biomedicines)
Background: Lung ischemia reperfusion injury (LIRI) is a severe complication after lung transplantation (LT). Ferroptosis contributes to the pathogenesis of LIRI. Maresin1 (MaR1) is an endogenous pro-resolving lipid mediator that exerts protective effects against multiorgan diseases. However, the role and mechanism of MaR1 in the ferroptosis of LIRI after LT need to be further investigated. Methods: A mouse LT model and a pulmonary vascular endothelial cell line after hypoxia reoxygenation (H/R) culture were established in our study. Histological morphology and inflammatory cytokine levels predicted the severity of LIRI. Cell viability and cell injury were determined by CCK-8 and LDH assays. Ferroptosis biomarkers, including Fe2+, MDA, 4-HNE, and GSH, were assessed by relevant assay kits. Transferrin receptor (TFRC) and Acyl-CoA Synthetase Long Chain Family Member 4 (ACSL4) protein levels were examined by western blotting. In vitro, lipid peroxide levels were detected by DCFH-DA staining and flow cytometry analysis. The ultrastructure of mitochondria was imaged using transmission electron microscopy. Furthermore, the potential mechanism by which MaR1 regulates ferroptosis was explored and verified with signaling pathway inhibitors using Western blotting. Results: MaR1 protected mice from LIRI after LTx, which was reversed by the ferroptosis agonist Sorafenib in vivo. MaR1 administration decreased Fe2+, MDA, 4-HNE, TFRC, and ACSL4 contents, increased GSH levels, and ameliorated mitochondrial ultrastructural injury after LTx. In vitro, Sorafenib resulted in lower cell viability and worsened cell injury and enhanced the hallmarks of ferroptosis after H/R culture, which was rescued by MaR1 treatment. Mechanistically, the protein kinase A and YAP inhibitors partly blocked the effects of MaR1 on ferroptosis inhibition and LIRI protection. Conclusions: This study revealed that MaR1 alleviates LIRI and represses ischemia reperfusion-induced ferroptosis via the PKA-Hippo-YAP signaling pathway, which may offer a promising theoretical basis for the clinical application of organ protection after LTx.